UU Pesantren: Local Genius dan Intervensi Negara terhadap Pesantren - Maulana Arif Setyawan (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2019)
There is no doubt that pesantrens have a real contribution to the development of education. Historically, they have extensive experiences in fostering and developing the community. In fact, pesantrens are able to increase their role independently by exploring the potential of the communities around them. Improving the role of pesantren is a strategic step in building national development goals, especially in the education sector. For this reason, to develop their potential, the government drafted pesantren and religious law. On the contrary, the draft of law raises anxiety among pesantrens because it is perceived to disturb their management. In addition, it may become the tool for government intervention in Islamic boarding school system, which in turn may loose their distinctive characteristics as a local genius education institution in Indonesia. This research is an analytical study with a qualitative approach. The study found that the Islamic Boarding School and Religious Education Law aims to form individuals who understand and practice the values ​​of their religion or become religious scholars who are faithful, pious, noble, knowledgeable, independent, ta'awun, tawazun and tawasut. The Islamic boarding school law has the advantage of being able to serve a clearer direction for the boarding school. However, its’ shortcomings are it open wider possibility of government interventions that may interfere household matters of the pesantrens too deeply, even though the pesantren is indeed an independent institution.